2020
DOI: 10.1093/ejcts/ezaa332
|View full text |Cite
|
Sign up to set email alerts
|

Safety of patients and providers in lung cancer surgery during the COVID-19 pandemic

Abstract: OBJECTIVES The coronavirus disease 2019 (COVID-19) pandemic has resulted in patient reluctance to seek care due to fear of contracting the virus, especially in New York City which was the epicentre during the surge. The primary objectives of this study are to evaluate the safety of patients who have undergone pulmonary resection for lung cancer as well as provider safety, using COVID-19 testing, symptoms and early patient outcomes. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…It thus seems that the percentage of hospital-acquired infections in our series of around 12,000 patients is very low, which tends to confirm the effectiveness of the measures taken to ensure the safety of these patients, in particular carrying out a PCR test on hospital admission. Several other publications studying LC surgery in the same period reported no infection, but these were performed in very small series [ 33 , 34 ]. In the literature, we found few results regarding SARS-CoV-2 infection during hospitalization for LC surgery, but we are also well aware that surgical inpatients were highly selected to ensure that they were free of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It thus seems that the percentage of hospital-acquired infections in our series of around 12,000 patients is very low, which tends to confirm the effectiveness of the measures taken to ensure the safety of these patients, in particular carrying out a PCR test on hospital admission. Several other publications studying LC surgery in the same period reported no infection, but these were performed in very small series [ 33 , 34 ]. In the literature, we found few results regarding SARS-CoV-2 infection during hospitalization for LC surgery, but we are also well aware that surgical inpatients were highly selected to ensure that they were free of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by evidence from national cancer registries [53,54]. Additionally, a recent study by Chang et al found that pulmonary resection for lung cancer can be safely performed in selected patients, even when performed in a hospital with a large COVID-19 census [55].…”
Section: Patients With Symptomatic or More Advanced Cancers Should Bementioning
confidence: 83%
“…If positive, we recommend 2 week quarantine followed by re-testing. During our experience from March 13th to May 4th, 2020, one (5%) of 21 patients was asymptomatic and found to be COVID-19 positive prior to surgery ( 30 ). Surgery was performed once the patient had a negative COVID-19 test.…”
Section: Management During Surge Phase or When Limited Hospital Capacmentioning
confidence: 96%
“…The outcomes of these criteria applied at the peak of COVID-19 pandemic to 21 patients at NYULH were retrospectively reviewed ( 30 ), and there were no major complications, 5 minor complications and average length of stay of 2 days. Twenty-four patients deferred surgery due to patient preference and only one of these patients progressed from T3N0 to T4N0 disease.…”
Section: Management During Surge Phase or When Limited Hospital Capacmentioning
confidence: 99%